Clean and new strategy for catalytic conversion of agriculture waste shells to activated carbon via microwave-assisted impregnation: Applied and eco-friendly aspect for decoloration of industrial corn syrup and process identifications. Issue 3 (June 2019) - Teimouri, Zahra; Salem, Amin; Salem, Shiva
Graphical abstract: Highlights: A clean strategy was proposed for conversion of agriculture shells to activated carbon. Microwave-assisted technique was used to impregnate catalyst on agriculture shells. The excellent decoloration performance was attributed to adsorption onto micropores. The proposed method is cost-effective in production of microporous activated carbon. The purified syrup is permissible as a sweetener in industrial applications. Abstract: The vast plantation of agriculture products leads to large amount of waste shells emanating from industrial processing which pose serious pollutions in lithosphere and atmosphere when is delivered by burning. In the present study, a clean and rapid method was demonstrated to develop a novel strategy for catalytic conversion of agriculture shells to microporous activated carbon as efficient adsorbent via microwave-assisted impregnation. In the proposed process, different contents of catalyst, zinc chloride, were impregnated on powdered shells, < 300 μm, by conventional and microwave-assisted techniques followed by carbonization of tar like materials in the normal and nitrogen atmospheres in sealed and open ceramic vessels, respectively. In order to realize the applicability of proposed catalytic conversion method, the produced activated carbons were employed in the decoloration of an industrial low grade corn syrup and the effects of technical factors such as catalyst impregnation ratio, microwave irradiation power, carbonization temperature and atmosphere were identified in real system. The catalyst should be impregnated in irradiation power of 600 W and carbonized at 500 °C to create the pores with average size of 2.4 nm in which the excellent decoloration performance, 94%, was achieved. The proposed method is not only rapid technique, 30 min, but also is cost-effective in the production of microporous activated carbon from bioresources in the normal closed vessel. The results revealed the most prominent advantage of activated carbon fabricated by microwave-assisted catalytic conversion compared to that prepared conventionally.